Ferroelectric Hf0.5Zr0.5O2 Thin Films Crystallized by Pulsed Laser Annealing. Issue 5 (7th April 2021) - Volodina, Natalia; Dmitriyeva, Anna; Chouprik, Anastasia; Gatskevich, Elena; Zenkevich, Andrei
Abstract : The crystallization of as‐grown amorphous Hf0.5 Zr0.5 O2 (HZO) thin films to the metastable ferroelectric phase by pulsed laser annealing (PLA) is investigated. PLA experiments are conducted using a Nd:YAG laser operating in two regimes: Q ‐switched mode with a pulse duration of τ ≈ 16 ns and free‐running mode ( τ ≈ 1 ms). The crystallization of a ferroelectric orthorhombic phase in the annealed films is confirmed by X‐ray diffraction, polarization versus electric field ( P–E ) measurements, and piezoresponse force microscopy (PFM) analyses. Remnant polarization up to 2 P r ≈ 50 μC cm −2 is achieved in the TiN/HZO/W capacitor structures grown on the Si substrate and subjected to millisecond PLA. In contrast, the use of laser annealing in a 10 ns pulse duration range is found ineffective for the crystallization of any HZO phase in capacitor structures. Detailed PFM analysis across a capacitor device area reveals the effect of the local temperature on the sample surface during PLA on the resulting ferroelectric domain structure. The lower thermal impact on the substrate during PLA opens the possibility of creating local areas of the ferroelectric phase in HZO films using reflecting copper masks. Abstract : Pulsed laser irradiation of a solid substrate results in extremely fast heating and cooling rates of a subsurface region, which gives rise to quenching of metastable phases during crystallization. The possibility of forming a ferroelectric phase in Hf0.5 Zr0.5 O2 (HZO) thin films by their crystallization with laser pulses of millisecond and nanosecond duration is demonstrated.